Getting C(0)

This way, C(0) = ε0, as the limit of α --> ωα

Up to C(Ω)

If ε0 = ωωω...(ω levels) = C(0), then ωωω....C(0)+1 (ω levels) = C(1), then ωωω....C(α)+1(ω levels)  = C(α+1).

This way, C(Ω) = ζ0


C(α) = Ψ(α).

Ad blocker interference detected!

Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.